Review Potensi Tanaman Pegagan (Centella asiatica L.) dalam Dunia Pengobatan Modern - Sodik, Jajang Japar; Saputro, M Ramadhan; Pahlevi, Muhamad Reza (Jurnal Farmasi Udayana, 2025)
For centuries, Asian countries have been using Centella asiatica to treat various types of diseases. Centella asiatica has been associated with its richness in biologically active compounds such as asiatic acid, asiaticoside, madecassic acid, and madecassoside. This literature review aims to explore Centella asiatica and its bioactive compounds towards human health. Based on the review of literature published in the last decade, it was found that asiaticoside obtained from Centella asiatica leaves is a compound with antioxidant, anti-inflammatory, and antimicrobial properties. The activity of asiaticoside plays a crucial role in maintaining human health and is used to prevent and treat various diseases, such as Neurodegenerative Diseases, Cardiovascular Disorders, and Skin Disorders. This literature review provides a fairly comprehensive overview of the benefits of Centella asiatica for human health, particularly summarizing methods and techniques for extracting Centella asiatica and providing an overview of the benefits of Centella asiatica for the treatment of common and chronic diseases, which is expected to be significant for medical literature..